Máxima fase estável de lactato sanguíneo e potência crítica em ciclistas bem treinados - Carita, R. A. C.; Greco, C. C.; Denadai, B. S. (Revista Brasileira de Medicina do Esporte, 2009)
The main objective of this study was to compare the intensity corresponding to the maximal lactate steady state (MLSS) and critical power (CP) in well-trained cyclists. Six male cyclists (25.5 ± 4.4 years, 68.8 ± 3.0 kg, 173.0 ± 4.0 cm) performed in different days the following tests: incremental exercise test until exhaustion to determine peak oxygen uptake (VO2peak) and its respective intensity (IVO2peak); five to seven constant workload tests to determine MLSS and CP and; one exhaustion test at CP. MLSS was defined as the highest workload at which blood lactate concentration did not increase by more than 1 mM between minutes 10 and 30 of the constant workload. Individual values for power-Tlim from the constant workload tests (95, 100 and 110% IVO2peak) were fit to the hyperbolic model of two-parameter to determine CP. Although highly correlated (r = 0.99; p = 0.0001), CP (313.5 + 32.3 W) was statistically higher than MLSS (287.0 + 37.8 W) (p = 0.0002). The percentual difference between CP and MLSS was 9.5 + 3.1 %. During exercise performed at CP, although a slow component of VO2 has developed (SC = 400.8 + 267.0 ml.min-1), the VO2peak was not attained (91.1 + 3.3 %). Based on these results, it can be concluded that CP and MLSS identify different exercise intensities, even in athletes with high fitness level. However, the percentual difference between CP and MLSS (9%) indicates that the relationship between these indexes may depend on aerobic fitness. During exercise performed at CP, the SC does not allow VO2peak to be attained.